Whole-genome bisulfite sequencing with improved accuracy and cost - Suzuki, Masako (Genome Res, 2018)
DNA methylation patterns in the genome both reflect and help to mediate transcriptional regulatory processes. The digital nature of DNA methylation, present or absent on each allele, makes this assay capable of quantifying events in subpopulations of cells, whereas genome-wide chromatin studies lack the same quantitative capacity. Testing DNA methylation throughout the genome is possible using whole-genome bisulfite sequencing (WGBS), but the high costs associated with the assay have made it impractical for studies involving more than limited numbers of samples. We have optimized a new transposase-based library preparation assay for the Illumina HiSeq X platform suitable for limited amounts of DNA and providing a major cost reduction for WGBS. By incorporating methylated cytosines during fragment end repair, we reveal an end-repair artifact affecting 1%–2% of reads that we can remove analytically. We show that the use of a high (G + C) content spike-in performs better than PhiX in terms of bisulfite sequencing quality. As expected, the loci with transposase-accessible chromatin are DNA hypomethylated and enriched in flanking regions by post-translational modifications of histones usually associated with positive effects on gene expression. Using these transposase-accessible loci to represent the cis-regulatory loci in the genome, we compared the representation of these loci between WGBS and other genome-wide DNA methylation assays, showing WGBS to outperform substantially all of the alternatives. We conclude that it is now technologically and financially feasible to perform WGBS in larger numbers of samples with greater accuracy than previously possible.